2015
DOI: 10.1007/s10517-015-2939-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Space Weather on Biomedical Parameters during the Solar Activity Cycles 23-24

Abstract: The results of long-term (1998-2012) biomedical monitoring of the biotropic effects of space weather are discussed. A drastic change in statistical distribution parameters in the middle of 2005 was revealed that did not conform to usual sinusoidal distribution of the biomedical data reflecting changes in the number of solar spots over a solar activity cycle. The dynamics of space weather of 2001-2012 is analyzed. The authors hypothesize that the actual change in statistical distributions corresponds to the ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There are many published works about the effects of space weather on human health. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) However, there are still many open questions about the specific parameters of space weather affecting the human body, and about the mechanisms of such influence.…”
Section: Introductionmentioning
confidence: 99%
“…There are many published works about the effects of space weather on human health. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) However, there are still many open questions about the specific parameters of space weather affecting the human body, and about the mechanisms of such influence.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Figure 2: The map of magnetic disturbances by the date of the space weather prediction center (swpc.noaa.gov) Furthermore, disturbances of the geomagnetic field can significantly affect human health and the biosphere as a whole. [18][19][20] However, some type's geomagnetic perturbations can play a positive role in the sphere of communication, and in-depth sensing of the earth, and prediction of earthquakes. [21,22] Thus, these problems cause more actively to explore the physics of such geophysical phenomena with the aim of the developing of the means of the monitoring, detection, prediction, and prevention of the occurrence of the geomagnetic disturbances and protection against these perturbations of the technical systems and the biosphere.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of long-term multi-latitude online monitoring of 2003-2015 from Yakutsk to Simferopol and Baku, simultaneous statistically signifi cant changes in the biomedical parameters were revealed, associated with variations in solar dynamics, geomagnetic fi eld and cosmic rays (total number of measurements is more than 500,000). 1-2 days after fl areups on the Sun, even in healthy people, a transition of heart dynamics to a more chaotic mode of functioning was observed [1,2]. A more detailed study of the heart dynamics in the phase space showed the division of the types of phase cardioportrait of the subjects into the "South Russian" (S) and…”
mentioning
confidence: 99%